(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Post-colonial historiography and historical fiction havecome to share common concerns about representation with post-modem historic-graphicmet fiction where story telling along with revelation in their own narrativelybecomes a historical and political act. As Simon argues, post- colonial writing becomes one of the ways of subverting imperial myths by ’foregrounding the fact that history is not a set of immovable pastachievements but a discourse, open toreinterpretation.’